Sorption of tetracycline on biochar derived from rice straw under different temperatures - Wang, Hua; Chu, Yixuan; Fang, Chengran; Huang, Fang; Song, Yali; Xue, Xiangdong (PloS one, 2017)
Biochars produced from the pyrolysis of waste biomass under limited oxygen conditions could serve as adsorbents in environmental remediation processes. Biochar samples derived from rice straw that were pyrolyzed at 300 (R300), 500 (R500) and 700°C (R700) were used as adsorbents to remove tetracycline from an aqueous solution. Both the Langmuir and Freundlich models fitted the adsorption data well (R2 > 0.919). The adsorption capacity increased with pyrolysis temperature. The R500 and R700 samples exhibited relative high removal efficiencies across a range of initial tetracycline concentrations (0.5mg/L-32mg/L) with the maximum (92.8%-96.7%) found for adsorption on R700 at 35°C. The relatively high surface area of the R700 sample and π-π electron-donor acceptor contributed to the high adsorption capacities. A thermodynamic analysis indicated that the tetracycline adsorption process was spontaneous and endothermic. The pH of solution was also found to influence the adsorption processes; the maximum adsorption capacity occurred at a pH of 5.5. These experimental results highlight that biochar derived from rice straw is a promising candidate for low-cost removal of tetracycline from water.